Adhesion Segmentation Algorithm and Fluorescence Intensity Extraction for Human Umbilical Vein Endothelial Cells (Journal of Fiber Bioengineering and Informatics, 2015)
Due to the complexity of adhesion and irregularity of human umbilical vein endothelial cells, we proposea novel cell image segmentation technique by combining cell image with corresponding nucleus imagebased on label-controlled watershed algorithm instead of segmenting the cell image directly. Moreover,nucleus segmentation and location in stained cells are introduced. The most fascinating advantage of thecombined method is its accurate positioning, which ensures that the center of each cell could be positionedaccurately and is conducive to the adhesion and irregular cells segmentation. To determine the activationtime of nuclear factor kappa B and its signaling pathway blocking mechanism, relevant fluorescenceparameters extraction approach is also discussed. Performance and result analysis demonstrate that thisalgorithm is valid, precise, and very helpful to further cell analysis and medical diagnosis.
Keywords: Human Umbilical Vein Endothelial Cells; Adhesion Segmentation; Nucleus Localization; Label-controlled Watershed Algorithm